2017
DOI: 10.1146/annurev-ecolsys-110316-022745
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Artificial Light at Night on Biological Timings

Abstract: The use of artificial lighting to illuminate the night has provided substantial benefits to humankind. It has also disrupted natural daily, seasonal, and lunar light cycles as experienced by a diversity of organisms, and hence it has also altered cues for the timings of many biological activities. Here we review the evidence for impacts of artificial nighttime lighting on these timings. Although the examples are scattered, concerning a wide variety of species and environments, the breadth of such impacts is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
174
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 194 publications
(175 citation statements)
references
References 107 publications
0
174
0
1
Order By: Relevance
“…Experimental lighting inhibited or encouraged the colonization of 39% of all taxa analyzed, including sessile and mobile species, leading to different community composition between lit and control sites. ALAN has also been shown to impact the niche space of species by extending the perceived day length and therefore activity patterns for diurnal species (Gaston et al., ). How significant this might be for community structure will depend on the extent to which species partition time during day and night for activity because of phylogenetic constraints, and the extent to which they do so to avoid or reduce competition or predation (which might mask underlying circadian rhythms).…”
Section: How Are Ecological Communities Affected?mentioning
confidence: 99%
“…Experimental lighting inhibited or encouraged the colonization of 39% of all taxa analyzed, including sessile and mobile species, leading to different community composition between lit and control sites. ALAN has also been shown to impact the niche space of species by extending the perceived day length and therefore activity patterns for diurnal species (Gaston et al., ). How significant this might be for community structure will depend on the extent to which species partition time during day and night for activity because of phylogenetic constraints, and the extent to which they do so to avoid or reduce competition or predation (which might mask underlying circadian rhythms).…”
Section: How Are Ecological Communities Affected?mentioning
confidence: 99%
“…These findings are the first to test how different non‐visual photoreceptors are stimulated by numerous anthropogenic light sources and reveal that numerous organisms are at risk for changes to circadian rhythms, seasonal reproduction, hormone cascades and immune function, phenology and migration (Kuenzel et al ., ; Gaston et al ., ; Alaasam et al ., ). We must emphasize that previous research has repeatedly shown that these non‐visual photoreceptors are directly responsible for changes in reproduction, physiology, immunity and phenology (Gaston et al ., ). The non‐visual photoreceptors captured millions of photons from these light sources, indicating that even though the light sources are long wavelength shifted, they will still alter organisms’ physiology and ecology.…”
Section: Discussionmentioning
confidence: 98%
“…Artificial light at night (ALAN; Gaston et al. ) may disrupt moonlight effects on pelagic larvae, yet the effects of cloud cover may be context‐dependent, as clouds can amplify the effects of ALAN near urban centers (Kyba et al. ).…”
Section: Discussionmentioning
confidence: 99%